The experience of a sample of individuals in the United Kingdom living in the pre‐manifest stage of Huntington's disease: An interpretative phenomenological analysis. Issue 2 (10th August 2021) - Wieringa, Gina; Dale, Maria; Eccles, Fiona J. R.
Abstract: This paper explores the experience of ten individuals living in the UK who were in the pre‐manifest stage of Huntington's disease (HD), a genetic neurodegenerative condition. Data were gathered using semi‐structured interviews and analyzed using interpretative phenomenological analysis. Three themes were reported from the data: 'feeling limited by time', 'the perception of stalling time', and 'making the most of time', all highlighting the way in which time holds significant meaning when living in the pre‐manifest stage of HD. This study has highlighted the difficulties experienced by individuals when adjusting to the pre‐manifest stage of HD. Feeling able to manage their anxieties and dealing with ongoing uncertainty related to future deterioration was key to supporting their wellbeing, facilitated by factors such as positivity and hope. Individuals may benefit from counseling which supports them to develop proactive coping strategies to manage their anxieties and acceptance of an uncertain future.